(untitled) (Advancements in Homeopathic Research, 2022)
The study is done on the topic “EXPLORING THE MIASMATIC APPROACH FOR WORK RELATED UPPER LIMB DISORDERS”. The objectives of this study are to study the details of work related upper limb disorders in computer users, to explore the underlying the miasms and to assess the effectiveness of homoeopathic remedies evolving after considering totality of symptoms in the treatment of ‘Work related upper limb disorders’ in computer workers.